Electrochemical Reactivity of KSi and NaSi Zintl Phases with Lithium. (1st January 2015) - Seznec, V.; Senguttuvan, P.; Larcher, D.; Tarascon, J.-M.
Abstract : The electrochemical reactions of NaSi and KSi Zintl phases with lithium (0–2.5 V) proceed very differently. Na/K is partially removed on first oxidation with a complete amorphization for NaSi or growth of a new crystallized Kx Si phase for KSi. Upon discharge, metallic K is partially extruded and a Li-K-Si (Li15 Si4 –type) phase is formed. For NaSi, metallic Na is also chased on discharge but crystallization of Li-Na-Si (Li15 Si4 –type) phase is delayed at the second discharge. The amorphization of Li15 Kx Si4 proceeds through a ∼0.40 Volts charge plateau but crystallized Li15 Nax Si4 does not show this feature and electrochemically behaves similarly to amorphous Lix Si.